PENGGUNAAN TEPUNG LIMBAH PENGALENGAN IKAN DALAM RANSUM TERHADAP PERFORMA BROILER - Baye, Arnold; Sompie, F. N.; Bagau, Betty; Regar, Mursye N. (Universitas Sam Ratulangi, 2015)
ABSTRACT UTILIZATION OF FISH MEAL CANNED WASTE PRODUCT ON BROILER PERFORMANCE. A research was conducted to evaluate the effects of fish meal utilization in the ration. The fish meal used canned fish waste product obtained from fish processingin Bitung North Sulawesi. This research used 60 broilers day old chick. Completely Randomized Design (CRD) cousisting of 4 treatments with 5 replications was used in this research. The treatments were 4 levels of fish meal in ration: R1=8%, R2=10%, R3=12%, and R4=14%. Biological variables measured to evaluate biological responses were feed consumption, body gain, and feed convertion. The result showed that there where no significant effect (P>0.05) on feed consumption (2647.40g – 2758.94g) and feed convertion (2.68 – 3.02), however there was a significant effect (P<0.05) of treatment on body gain (879.80g – 1032.20g). Honestly Significant Difference test showed that 14% fish meal in ration (1032.20 g) was significantly higher compare to 8% fish meal (879.80g), however 8%, 10%, and 12% fish meal in the ration were not significantly. It can be concluded that fish meal of canned fish waste product can be used up to 14% in the ration. Keywords : fish meal, fish canned waste, broiler performance